From Lab to Clinic: Controlled Drug Delivery Mechanisms and Translational Challenges - Jaiswal, Pinky; Chaudhary, Shaily; Muwel, Madhuri; Fareliya, Mahima; Dueby, Mahak; Mulewa, Mayuri; Dhakad, Lucky; Choyal, Mohit; Nagar, Lakhan; Yadav, Akash (Journal of Neonatal Surgery, 2025)
Controlled drug delivery systems (CDDS) are designed to release therapeutic agents at precise rates, locations, and durations to enhance treatment efficacy and minimize side effects. Traditional drug delivery methods have several limitations, including high dosage frequency, difficulty in dose monitoring, and non-specific administration. CDDS address these issues by ensuring targeted delivery, improved bioavailability, and reduced dosing frequency. Excipients play a crucial role in CDDS, with polymers, lubricants, and binding agents being key components. Polymers, both synthetic and natural, help regulate drug release, enhance stability, and improve patient compliance. CDDS function based on various mechanisms, including dissolution-controlled, diffusion-controlled, and water penetration-controlled systems. Advanced techniques such as nanoparticle-based delivery, osmotic-controlled systems, and biodegradable polymers further enhance drug delivery efficiency. Pharmacokinetics and pharmacodynamics govern drug absorption, distribution, metabolism, and excretion, influencing bioavailability and therapeutic outcomes. Factors such as molecular weight, solubility, partition coefficient, and pKa affect drug performance in controlled formulations. Compared to conventional drug delivery systems, CDDS maintain plasma drug concentration within the therapeutic window, reducing toxicity risks and enhancing patient compliance. Applications of CDDS span multiple medical fields, including chronic disease management, neurological disorders, hormone therapy, cardiovascular treatments, and antibiotic delivery. Emerging technologies such as nano-medicine, microfluidics, molecularly imprinted polymers, CRISPR/Cas9, and quantum sensing are revolutionizing drug delivery. Additionally, advancements in 3D printing enable customized dosage forms tailored to patient needs. Despite these advancements, challenges remain, including potential toxicity, formulation complexity, and high production costs. Future research aims to improve biocompatibility, develop intelligent biomaterials, and refine personalized medicine approaches. The continuous evolution of CDDS holds promise for more effective and patient-friendly therapeutic solutions.